Budaya Organisasi - Habudin, Habudin (Program Studi S3 Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
Organizational culture is an important and very strategic element in the development and progress of organizations in both business, government, educational institutions, and religious social organizations. This paper aims to describe the culture of the organization through theoretical analysis and empirical analysis. Especially the culture of organizations related to Islamic educational institutions. The study is divided into 3 (three) sections. One, an introduction outlining issues related to the culture of the organization as well as the significance of the paper written. Second, the Discussion outlines expert opinions supported by empirical data and information then constructed by the authors so that the direction of this paper is more specific to the objectives that it wants to achieve. Third, The Cover is a conclusion of the issues and discussions that have been outlined. This paper concludes that the development and existence of the organization has a strong and significant relationship with the culture of the organization